Analisis Fasilitas Pelayanan Penumpang Disabilitas Di Bandar Udara Domine Eduard Osok Sorong - Andi Andini Armayanti; Suprapti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Abstract: In providing facilities for the convenience of airport service users, the airport should provide facilities not only for public facilities but facilities that are friendly for passengers with disabilities and also in accordance with existing regulations. This study aims to find out: How are the Disabled Passenger Service Facilities provided by Domine Eduard Osok Sorong Airport. In this study, researchers only limited it to the terminal area of Domine Eduard Osok Sorong Airport, where it is a place for passengers to carry out activities before boarding the plane. This study used qualitative research methods. Data collection techniques used are observation, interviews and documentation. Researchers directly make observations in the field as well as do documentation. For interviews, researchers did it to 3 sources. The data analysis technique used is data collection, data reduction, data presentation, discussion and conclusion. The results of this study indicate that there are still several disabled passenger facilities that are not yet available at Domine Eduard Osok Sorong airport. The facilities provided by the airport are also sufficient for easy access for passengers with disabilities. Disability facilities are very important to support the activities of disabled passengers at the airport.